(3JMaI SjOi CMeO Hf YWGA Gddg GdScfOQis - (3CMeO Hf eMeO Hf YHO GdcQje Hf YWGA Gddg GdScfOQj, GHf YWGA Gddg , JGL GdOjf CHh GdaVd,J (B709 (3g` s
(3ChdgG (B:s
(3bGd GdTjN Hf YWGAGddg GdScfOQj CjgG GdYHO CWdH GdJhHI ef Gddg JYGdj aj cd hbJ bGd JYGdi (B: (3hJhHhG Edi Gddg LejYkG CjgGGdeDefhf dYdce JadMhf s
(3BNQgG (B:s
(3ZjQ hGVM s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B221 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B121s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JUha (B154) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs